Domestic tourist motivation assessment in I-City Shah Alam - Ab Rahman, Syakir Amir (IIUM Press, 2019)
The theme park is one of the tourism products in Malaysia that generate income to the country as well has been selected as the prior destination among tourists as it is one of the famous attraction sites for the purpose of leisure, recreational, entertainment activities. It is important for the theme park operators to understand the motivations that lead the visitors to come to their places. This paper presents the relationship between domestic tourists’ demographic characteristics and their frequency of visit to I-City, Shah Alam. Total of 150 respondents involved for the questionnaire survey. The result shows the purpose of recreation and relaxation is the main motivations that motivate their visit to the study area. It is also found that most of the domestic tourists are young, single and living nearer to the Shah Alam region. Adopting few strategies like introducing new themes, games and attractions that compatible with every age group and improving the accessibility by providing I-City Shuttle Bus will help to increase the number of tourist arrival and tendency to revisit more in the future. The research gives benefits and provide information to the authoritative body as well as industry players, especially I-City’s management, and Tourism Selangor in order to contribute more to the related tourism products besides for the educational references for the future.